Acute ataxia in children: etiological spectrum and clinical characteristics - Zhao, Qing; Gao, Chao; Wang, Lihui; Liu, Chong; Sun, Suzhen; Li, Baoguang (Frontiers in Pediatrics, 2025)
BackgroundAcute ataxia is one of the most common movement disorders in children, characterized by complex etiologies, some of which may lead to disability or life-threatening complications. Early diagnosis and intervention are therefore crucial.ObjectiveThis study aimed to investigate the etiological spectrum and clinical characteristics of children presenting with acute ataxia as the initial symptom.MethodsA retrospective analysis was conducted on children hospitalized at Hebei Children's Hospital between January 2018 and December 2024, all of whom exhibited acute ataxia as the primary manifestation. Clinical data, including etiology, age distribution, and laboratory findings, were systematically reviewed and analyzed.ResultsA total of 257 children were included, with a male-to-female ratio of 1.14:1 and a median age of onset of 3 years (range: 10 months to 14 years). Initial screening of 315 records identified 58 patients for exclusion. Etiologies varied by age: infants/toddlers (0–3 years) showed acute postinfectious cerebellar ataxia (APCA, 66%), drug intoxication (14%), and acute disseminated encephalomyelitis (ADEM, 8%); preschoolers (4–6 years) had APCA (63%), ADEM (14%), and acute cerebellitis (AC, 8%); school-aged children (7–14 years) presented APCA (48%), AC (21%), and drug intoxication (14%). AC patients exhibited later onset, longer duration from symptom onset to hospital presentation, and more frequent neurological symptoms (encephalopathy, headache, vomiting) compared to APCA. Cerebrospinal fluid (CSF) nucleated cell counts were elevated in AC. Among APCA cases, CSF oligoclonal band (OCB)-positive patients had later onset, extended hospitalization, higher CSF nucleated cell counts, and higher relapse rates. Autoantibody screening in a subset of 135 patients identified CSF OCB, serum myelin basic protein (MBP), myelin oligodendrocyte glycoprotein (MOG) immunoglobulin G (IgG), GQ1b, and aquaporin-4 (AQP4) antibodies as common markers.ConclusionThe etiology of acute ataxia in children varies significantly by age, necessitating tailored diagnostic approaches. For cases suggestive of central nervous system demyelination or recurrent ataxia, comprehensive evaluations, including autoantibody testing, tumor screening, and genetic/metabolic assessments, should be considered to guide management and improve outcomes. CSF OCB positivity may identify an APCA subgroup with more pronounced inflammatory features and a potentially higher relapse risk.